Variáveis fiscais e PIB per capita no Brasil: Relaç\~oes vigentes entre 1901 e 2006 - Alexandre Manoel Angelo da Silva; Angelo José Mont'Alverne Duarte (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper analyses primary revenue, primary expenditure, public investment and public consumption from Brazilian federal government by Markov Switching Vector Autorregressive methodology (MS-VAR), investigating if these fiscal variables are procyclical or countercyclical in relation to Brazil Gross Domestic Product (GDP) per capita, in the period 1901 to 2006. Results suggest two important conclusions. First, the Brazilian federal government is wasteful. In fact, while the real growth rate from primary expenditure grew 7.7% year-over-year, the GDP per capita grew 5.09% year-over-year. Second, in the Brazilian federal government, there is only one fiscal regime, which is the procyclical regime between the primary expenditure and the GDP per capita.
Keywords: H50; E62; C32; 330